Rancang Bangun Aplikasi Sistem Pakar Diagnosa Hama Dan Penyakit Pada Tanaman Cabai Berbasis Web - Afrianti, Dedeh Kurnia; Marpaung, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Chili plant is a plant that is widely cultivated by the Farmers in Indonesia. However, chili plant is a plant susceptible to attack of Plant Disturbing Organisms (pests and diseases). Pest and disease attack causes decrease productivity and harvest fail. To overcome this, proper control is required. Therefore, an expert in the field is required. This research designs and builds an expert system application using Bayes Theorema probability method. This expert system is implemented in the website, so it can be easily acceessed by user. This system diagnoses attacks from the selected symptoms, then the system calculates the probability of each symptom, and displays the result of the attack name and the percentage of the outbreak of the attack. The result of this research is the expert system application can be used to diagnose pest and disease chili plant and help the chili Farmers in finding the solutions to problems about the pests and diseases of chili plants.Keywords : expert system, chili plants, pest and disease, Bayes Theorema.